SPE Annual Technical Conference and Exhibition 2015
DOI: 10.2118/175159-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Thorough Investigation of Mechanisms of Enhanced Oil Recovery by Carbonated Water Injection

Abstract: The benefits and advantages of waterflood are well-known with many decades of application in a wide range of reservoirs with different crude oil and rock types. However, the average global recover factor for waterflood is only around 30%. There is, therefore, great interest in developing methods that can augment waterflood and improve its recovery factor from the current low values. It has been shown that enriching water with CO2 and injecting it in the form of carbonated water can improve the performance of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 7 publications
2
86
0
Order By: Relevance
“…In the 1960s, commercial applications of CWI in Oklahoma, Texas, and Kansas demonstrated that CWI resulted in increased water injectivity and oil recovery [2]. In more recent studies, the CWI phenomenon has been visualized in glass micromodels [1,3,4]. These studies confirmed oil swelling, oil viscosity reduction, and the generation of CO 2 -enriched gas during CWI.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the 1960s, commercial applications of CWI in Oklahoma, Texas, and Kansas demonstrated that CWI resulted in increased water injectivity and oil recovery [2]. In more recent studies, the CWI phenomenon has been visualized in glass micromodels [1,3,4]. These studies confirmed oil swelling, oil viscosity reduction, and the generation of CO 2 -enriched gas during CWI.…”
Section: Introductionmentioning
confidence: 87%
“…When carbonated water (CW) comes into contact with oil, the CO 2 dissolved in CW moves into the oil, resulting in oil viscosity reduction and swelling [1]. These effects depend on the CO 2 solubility of brine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] However, the reduction in interfacial tension and thus wettability alteration toward more water-wet can be another positive effect of CWI compared to the water injection process in oil reservoirs. [22,[29][30][31] Sohrabi et al also investigated the potential of CWI under reservoir conditions, by using a live oil sample (dead oil is saturated with methane). Increasing the carbonation level caused oil recovery enhancement and this effect was found to be profound in low API oils.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 -saturated water flooding may have a better performance over direct injection of CO 2 because of its higher sweep performance [5]. In water flooded reservoirs, CO 2 -saturated water flooding can alleviate the adverse effect of high water saturation and the water shielding effect as a result of mixing with the resident water [6][7]. This might, in turn increase the rate of CO 2 diffusion into the oil and the subsequent oil swelling.…”
Section: Introductionmentioning
confidence: 99%